Adolescents, well-being and spirituality: insights from a spiritual program - Pandya, Samta P. (International journal of children's spirituality, 2015)
This paper is a study of adolescents, well-being and spirituality. I have looked at the All Round Training in Excellence (ART-Excel) program for adolescents developed by an international spiritual organisation called the Art of Living Foundation (AOL Foundation). Adolescents participants (n = 396) of this program from four cities - Vancouver, London, Johannesburg and Mumbai - comprised of the sample. An equal number comprised of the control group. The findings suggest that spirituality is generally perceived as having positive mental health and well-being influences for program participants. Logistic regression analyses showed that girls, Hindus (homeland and Diaspora), adolescents in higher monthly expenses brackets, with a better health status, that is no self-declared ailments saw a higher efficacy to the ART-Excel program. The program was in general seen to contribute to well-being, social participation, sense of social duty, relationships, future vision and educational attainment. It is important to recognise the role of spirituality in early adolescents' psychological well-being and include discussion of such coping mechanisms in working with this population. Moving this further it is also important for helping professionals to be cognisant of the possible presence and importance of spiritual beliefs in the lives of troubled adolescents such as runaway and homeless youth.